Breast Reconstruction with Enhanced Stromal Vascular Fraction Fat Grafting. Issue 6 (June 2015) - Gentile, Pietro; Scioli, Maria Giovanna; Orlandi, Augusto; Cervelli, Valerio
<x xml:space="preserve">Abstract</x> Background: Actually, there are 2 main methods to obtain stromal vascular fraction (SVF): enzymatic digestion and mechanical filtration; however, the available systems report heterogeneous and sometimes not univocal results. The aim of this study is to evaluate different procedures for SVF isolation and compare their clinical efficacy in the treatment of soft-tissue defects in plastic and reconstructive surgery. The authors evaluated Celution and Medikhan, enzymatic systems, and Fatstem and Mystem system, mechanical separation systems. Methods: Fifty patients affected by breast soft-tissue defects were treated in the Plastic and Reconstructive Surgery Department of Tor Vergata University of Rome. Four groups of 10 patients were managed with enhanced SVF fat grafts using cells obtained by Celution (Cytori Therapeutics, Inc., San Diego, Calif.), Medikhan (Medi-Khan Inc., West Hollywood, Calif.), Fatstem (Fatstem CORIOS Soc. Coop, San Giuliano Milanese, Italy), and Mystem (Mystem evo Bi-Medica, Treviolo, Italy) systems. A control group of 10 patients was treated with only centrifuged fat according to Coleman's technique. Results: In enhanced SVF–treated patients treated with cells obtained by Celution system, we observed a 63% ± 6.2% maintenance of contour restoring after 1 year, compared with 39% ± 4.4% of control group. In patients treated with SVF obtained by Medikhan system, we observed a 39% ± 3.5% maintenance, whereas enhanced SVF with Fatstem and Mystem systems gave a 52% ± 4.6% and 43% ± 3.8% maintenance of contour restoring, respectively. SVF cell counting indicated that Celution and Fatstem were the most efficient systems to obtain SVF cells. Conclusions: Celution and Fatstem were the 2 best automatic systems to obtain SVF and to improve maintenance of fat volume and prevent the reabsorption.